خريطة تطور كتب دروس اللغة العربية في إندونيسيا: دراسة تحليليية في الكتب المدرسية لمحمود يونس - Yusuf Salam, Muhammad (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
This study aims to reveal: first the background of the preparation of Indonesian-based Arabic teaching materials, second: Mahmud Yunus' method in an effort to develop Arabic teaching materials for Indonesians. This study uses a qualitative design, with a literature approach that comes from historical, social and educational sources. The research data were obtained using documentation, observation, and in-depth interviews. The data collection of this research depended on library sources on the history of the compilation and content of Arabic textbooks by Mahmud Yunus for Indonesian students. The data is then validated for correctness, suitability and reliability through data triangulation. This study resulted in the findings describing Mahmud Yunus' reform efforts in the development of Arabic teaching materials in Indonesia, as follows: First, the birth of Arabic textbooks was based on the results of Mahmud Yunus' study which showed that the Arabic language book material that came from Middle East was not based on student needs. Indonesia, and the two textbook materials compiled by Mahmud Yunus are contextualized, and oriented towards student life.